ENGLISH TEACHERS’ PERSPECTIVES ON THE INTEGRATION OF PROCESS GENRE APPROACH AND MULTIMODAL COMPOSITION IN EFL ESSAY WRITING - Khidayatul Munawwaroh; Refnaldi Refnaldi; Hamzah Hamzah (English Study Program University of Pasir Pengaraian, 2026)
This study investigates teachers’ perspectives on integrating the Process-Genre Based Approach (PGBA) and multimodal composition in EFL essay writing instruction. It addresses the gap between theoretical developments in writing pedagogy and their implementation in classroom practice. A qualitative descriptive design was employed involving ten university-level English teachers. Data were collected through questionnaires and semi-structured interviews. The findings reveal that teachers have a positive understanding of PGBA and acknowledge the importance of multimodal composition in enhancing student engagement and supporting learning in the digital era. However, the actual integration of PGBA and multimodal elements in classroom practice remains limited. Several challenges were identified, including limited teaching materials, insufficient training, time constraints, and low confidence in using technology. The study also highlights teachers’ strong need for practical support, particularly integrated coursebooks and clear instructional guidelines. Overall, the findings emphasize the importance of systematic support to facilitate the effective implementation of innovative approaches in EFL writing instruction..